KAMPUNG SEHAT, UMKM BERKEMBANG: KOLABORASI SOSIALISASI STUNTING DAN PENDAMPINGAN UMKM DI DESA CIBOLANG KALER: - Rahmawati, Lina (Jurnal Abdi Nusa, 2025)
In 2014, Sukabumi Regency recorded 21,795 micro businesses, 4,328 SMEs, and 877 medium businesses in the MSME sector. The number of workers absorbed reached 68,668 people and the distribution included food and beverage, trade, services, leather crafts, knitting, and other fields. However, the promotion efforts for MSMEs carried out by the Sukabumi Regency Government have only covered 3,933 of the 27,000 existing MSMEs. In the digital era, adapting to rapid business changes is very important, especially in the context of digital technology. Cibolang Kaler Village is located in Cisaat District, Sukabumi Regency, West Java, with a population of 10,931 people. This village is divided into 3 settlements with 9 RWs. Due to its strategic location, Cibolang Kaler Village is at the heart of economic and social development efforts in the region. Therefore, we created various innovations through observation methods, interviews, introduction to digital marketing, planning, implementing, and publishing logo and banner designs, as well as applying the canvas business model and SWOT analysis. All of these steps are part of a strategy that aims to encourage MSMEs towards digitalization to increase their effectiveness and marketing performance. Apart from MSMEs, stunting is also a significant threat to the quality of Indonesian society because apart from disrupting physical growth, children also experience brain development disorders which will affect their abilities and achievements. Apart from that, children who suffer from stunting will have a history of poor health due to flawed immune systems. Cibolang Kaler village has several toddlers affected by stunting in the Cisaat District. This can be proven by the number of toddlers affected by stunting, namely 3 toddlers. The method used in implementing stunting management activities in Cibolang Kaler Village is the method of counseling and socializing activities involving community members in Cibolangkaler Village. Implementation begins by looking for data on community needs, followed by designing ideas regarding these problems. After the design is perfect, the activity continues with implementing these ideas with the hope that what has been implemented will be utilized optimally by the community members in Cibolang Kaler Village. Keywords: Brand Strengthening, Simping MSMEs, Stunting, Stunting prevention